Assessment of freeze damage in fruits and vegetables. (July 2019) - Jha, Piyush Kumar; Xanthakis, Epameinondas; Chevallier, Sylvie; Jury, Vanessa; Le-Bail, Alain
Abstract: Freezing is an efficient and widely used method of food preservation. However, it can also cause irreversible damages at cellular level which in turn degrade the overall quality of the frozen food products. Therefore, qualitative and quantitative methods and technologies that will be able to evaluate with accuracy the freeze damage are of great importance. This review paper provides a comprehensive study of the methods that have been used to evaluate the freeze damage in fruits and vegetables. Further than the principles and the applications of those methods, the advantages and the limitations are also being discussed. Graphical abstract: Unlabelled Image Highlights: Freeze damage mechanism in fruits and vegetables is discussed. Factors governing the freeze damage are introduced. Methods used to assess the freeze damage at cellular level are presented. Assessment methods for macro/ meso freeze damage level are presented.